2019
DOI: 10.3766/jaaa.18002
|View full text |Cite
|
Sign up to set email alerts
|

Eustachian Tube Dysfunction and Wideband Absorbance Measurements at Tympanometric Peak Pressure and 0 daPa

Abstract: Although wideband absorbance (WBA) provides important information about middle ear function, there is limited research on the use of WBA to evaluate eustachian tube dysfunction (ETD). To date, WBA obtained under pressurized condition has not been used to evaluate ETD.The objective of the study was to compare WBA at 0 daPa and tympanometric peak pressure (TPP) conditions in healthy ears and ears with ETD.A cross-sectional study design was used.A total of 102 healthy ears from 79 participants (mean age = 10.0 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 38 publications
3
14
2
Order By: Relevance
“…40 Absorbance results of the present study are in agreement with other studies that reported absorbance being reduced at ambient pressure and returning to normal levels at TPP in ears with negative middle ear pressure. 19,41 Using an experimental model, Pau et al 18 reported that tympanometry in ears with RPs or atelectasis does not measure middle ear pressure correctly. The TPP depends on the size of the RP and the remaining gas volume in the middle ear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Absorbance results of the present study are in agreement with other studies that reported absorbance being reduced at ambient pressure and returning to normal levels at TPP in ears with negative middle ear pressure. 19,41 Using an experimental model, Pau et al 18 reported that tympanometry in ears with RPs or atelectasis does not measure middle ear pressure correctly. The TPP depends on the size of the RP and the remaining gas volume in the middle ear.…”
Section: Discussionmentioning
confidence: 99%
“…WBA, measured at ambient pressure (WBA) or under pressurized conditions (wideband tympanometry, WBT) performs better than the single frequency tympanometry in identifying middle ear pathologies such as otosclerosis, otitis media with effusion (OME), and eustachian tube dysfunction. 12,[19][20][21][22] To date, there are no studies that have systematically investigated WBA or WBT in ears with RPs or cholesteatomas. As a sensitive measure of middle ear function, WBA may shed light on specific pathological changes of RPs and cholesteatomas.…”
mentioning
confidence: 99%
“…WBT performed under pressurised conditions has the potential to improve the accuracy of detecting middle ear disorders [7]. Aithal et al (2018) measured WBA 0 and WBA TPP in 43 ears with Eustachian tube dysfunction and 102 ears with normal middle ear function. They reported that ears with Eustachian tube dysfunction had reduced WBA 0 between 0.6 and 1.5 kHz compared to WBA TPP .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, creating a dichotomous outcome from a disease that lies on a spectrum can lead to loss of information. Furthermore, there is growing evidence that WAI can detect mild pathology such as Eustachian tube dysfunction, as well as more severe conditions such as otitis media with effusion (Aithal, Aithal, Kei, Anderson, & Liebenberg, 2018;Beers et al, 2010;Ellison et al, 2012;Hunter et al, 2008b;Robinson, Thompson, & Allen, 2016;Shaver & Sun, 2013;Voss, Merchant, & Horton, 2012;Werner et al, 2010). Studies of infants and children have found a systematic decrease in A as the severity of middle ear disease increases Ellison et al, 2012;Hunter et al, 2008b).…”
Section: Predictive Modellingmentioning
confidence: 99%
“…There is growing evidence that WAI can detect mild pathology such as Eustachian tube dysfunction, as well as more severe conditions such as otitis media with effusion (Aithal et al, 2018;Beers et al, 2010;Ellison et al, 2012;Hunter et al, 2008b;Myers et al, 2018aMyers et al, , 2018bRobinson et al, 2016;Shaver & Sun, 2013;Voss et al, 2012;Werner et al, 2010). Studies of infants and children have found average absorbance or reflectance for mild cases falls between results for healthy ears and ears with severe middle ear dysfunction from 1000 to 6000 Hz Ellison et al, 2012;Hunter et al, 2008b;Myers et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%